A study on the anti-allergic effects of the native probiotic isolates on β-histine hydrochloride induced mice model (Bangladesh Journal of Livestock Research, 2020)
This study aimed to screen anti-allergic effect of native probiotics isolated from yoghurt. The probiotic bacteria were isolated from the yoghurt sample collected from seven Divisions of Bangladesh. The isolated probiotic bacteria were then subjected to morphological and biochemical tests. These morphological and biochemical tests allowed us to ensure that the isolated bacteria were the probiotic type. Then animal trial was conducted using these probiotic isolates. In this study, mice were used as the animal model. At the end of the trial, the blood samples isolated from different mice groups were analyzed. It was observed that, the probiotic isolates had significant effect (p0.05) on the eosinophil count and peripheral lymphocyte count of the mice used this experiment. It is recommended that, probiotic yoghurt may be used for allergic patients to cure allergic reactionBangladesh J. of Livestock Res. 21-25: 36-44, 2018